2013
DOI: 10.4141/cjss2012-071
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms leading to enhanced soil nitrous oxide fluxes induced by freeze–thaw cycles

Abstract: Risk, N., Snider, D. and Wagner-Riddle, C. 2013. Mechanisms leading to enhanced soil nitrous oxide fluxes induced by freeze–thaw cycles. Can. J. Soil Sci. 93: 401–414. The freezing and thawing of soil in cold climates often produces large emissions of nitrous oxide (N2O) that may contribute significantly to a soil's annual greenhouse gas emission budget. This review summarizes the state of knowledge of the physical and biological mechanisms that drive heightened N2O emissions at spring melt. Most studies of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
66
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(71 citation statements)
references
References 115 publications
4
66
0
1
Order By: Relevance
“…This is consistent with other studies from southern Alberta, Canada, which showed peak N 2 O fluxes during winter (Hao, 2015) or the late-winter to spring period (Chang et al, 1998;Ellert and Janzen, 2008) during the non-growing season. Typically, N 2 O fluxes are greatest during the spring snowmelt in temperate regions (WagnerRiddle and Thurtell, 1998;Johnson et al, 2012;Risk et al, 2013;Congreves et al, 2016). However, our study location typically does not accumulate much snow over-winter.…”
Section: Nitrous Oxide Emissionsmentioning
confidence: 99%
See 4 more Smart Citations
“…This is consistent with other studies from southern Alberta, Canada, which showed peak N 2 O fluxes during winter (Hao, 2015) or the late-winter to spring period (Chang et al, 1998;Ellert and Janzen, 2008) during the non-growing season. Typically, N 2 O fluxes are greatest during the spring snowmelt in temperate regions (WagnerRiddle and Thurtell, 1998;Johnson et al, 2012;Risk et al, 2013;Congreves et al, 2016). However, our study location typically does not accumulate much snow over-winter.…”
Section: Nitrous Oxide Emissionsmentioning
confidence: 99%
“…Furthermore, the solubility of N 2 O is inversely related to temperature, water at 0°C will contain about twice the N 2 O as water at 20°C (Weiss and Price, 1980). This may partly contribute to soils near 0°C emitting unexpectedly large quantities of N 2 O, as diffusion gradients between the dissolved pool of N 2 O and the atmosphere may drive degassing of N 2 O during warming events (Goodroad and Keeney, 1984;Risk et al, 2013). However, N 2 O fluxes persisted even when soil temperatures did not rise above the freezing point.…”
Section: Nitrous Oxide Emissionsmentioning
confidence: 99%
See 3 more Smart Citations